A Hierarchically Nanostructured Cellulose Fiber‐Based Triboelectric Nanogenerator for Self‐Powered Healthcare Products. (19th September 2018) - He, Xu; Zou, Haiyang; Geng, Zhishuai; Wang, Xingfu; Ding, Wenbo; Hu, Fei; Zi, Yunlong; Xu, Cheng; Zhang, Steven L.; Yu, Hua; Xu, Minyi; Zhang, Wei; et al.
Abstract: Rapid progress in nanotechnology allows us to develop a large number of innovative wearables such as activity trackers, advanced textiles, and healthcare devices. However, manufacturing processes for desirable nanostructure are usually complex and expensive. Moreover, materials used for these devices are mainly derived from nonrenewable resources. Therefore, it poses growing problems for living environment, and causes incompatible discomfort for human beings with long‐time wearing. Here, a self‐powered cellulose fiber based triboelectric nanogenerator (cf‐TENG) system is presented through developing 1D eco‐friendly cellulose microfibers/nanofibers (CMFs/CNFs) into 2D CMFs/CNFs/Ag hierarchical nanostructure. Silver nanofibers membrane is successfully introduced into the cf‐TENG system by using CMFs/CNFs as template, which shows excellent antibacterial activity. Enabled by its desirable porous nanostructure and unique electricity generation feature, the cf‐TENG system is capable of removing PM2.5 with high efficiency of 98.83% and monitoring breathing status without using an external power supply. This work provides a novel and sustainable strategy for self‐powered wearable electronics in healthcare applications, and furthermore paves a way for next‐generation flexible, biocompatible electronics. Abstract : The introduction of 1D eco‐friendly cellulose microfibers/nanofibers (CMFs/CNFs) into 2D CMFs/CNFs/Ag hierarchical nanostructure for a self‐powered triboelectric nanogenerator system enables the device with high efficiency for PM2.5 removal (98.83%), excellent antibacterial activity, and monitoring breathing without an external power supply, due to desirable pores/nanofibers design in the hierarchical nanostructure and a unique electricity generation feature of the device.